2016
DOI: 10.3892/ijo.2016.3347
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9: An anticancer molecule for gallbladder carcinoma

Abstract: Abstract. Gallbladder cancer (GBC) is the most common and aggressive type of biliary tract cancer. There are various histological types of GBC, and the vast majority of GBC cases are adenocarcinomas. Squamous and adenosquamous carcinomas are rare GBC subtypes that are traditionally considered to be more aggressive and to be associated with a poorer prognosis than adenocarcinoma. Galectin-9 (Gal-9), a tandem-repeattype galectin, has been reported to induce apoptosis-mediated elimination of various cancers, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
(50 reference statements)
2
28
0
Order By: Relevance
“…Depending on the nature and distribution of IgE receptors, different functions might be envisaged. Galectin‐3 is well recognized for its contribution to tumour progression and metastasis development , while galectin‐9 seems to have antiproliferative effects . The trimeric FcεRI(αγ2) showed membranous and cytoplasmic expression in intestinal epithelial cells and a prominent FcεRI α‐chain expression was also found in the Paneth cells of patients with cancer of the proximal colon.…”
Section: Ige Receptor Expression On Immune Cells and Epithelial Cellsmentioning
confidence: 99%
“…Depending on the nature and distribution of IgE receptors, different functions might be envisaged. Galectin‐3 is well recognized for its contribution to tumour progression and metastasis development , while galectin‐9 seems to have antiproliferative effects . The trimeric FcεRI(αγ2) showed membranous and cytoplasmic expression in intestinal epithelial cells and a prominent FcεRI α‐chain expression was also found in the Paneth cells of patients with cancer of the proximal colon.…”
Section: Ige Receptor Expression On Immune Cells and Epithelial Cellsmentioning
confidence: 99%
“…Clinical symptoms arise late in the course of the disease, 30-40 years after asbestos exposure, when the efficacy of therapeutic interventions is limited. In this study, we found that human MM tumors express high levels of galectin-9, a lectin that recently emerged as a promising target for cancer immunotherapy due to its dual role in cancer cell apoptosis [5][6][7][8][9][10][11] and TAMs differentiation. 14,38 We generated and tested a novel P4D2 mAb that binds galectin-9 C-terminal CRD and shows unique agonistic properties with recombinant galectin-9 in inducing cancer cell apoptosis and in modulating macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Treatment with recombinant galectin-9 has been demonstrated to interact with these lattice structures and promote apoptosis in different types of tumor cells. [5][6][7][8][9][10][11] In our preliminary experiments, we observed that both human and mouse MM cells express surface galectin-9 ( Supplementary Figure 1a-c) and therefore investigated if P4D2 and P1D9 mAbs could mimic the apoptotic effect induced by recombinant galectin-9. We assayed two human MM cell lines (Mill and ROB) and two mouse MM cell lines (CRH5 and EOH6).…”
Section: P4d2 Has Agonistic Properties and Induces Apoptosis Of MM Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Galectin-9 has been reported to exert anticancer activity in gallbladder cancer by modulation of the miRNA expression profile [125]. On the other hand, in liver cancer, galectin-9 is overexpressed because of miR-22 downregulation.…”
Section: Epigenetic Regulation Of Sugar Binding Molecules: the Galmentioning
confidence: 99%